1998
DOI: 10.1007/bf02387304
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the purity and irradiation stability of Cyanex 301 on the separation of trivalent actinides from lanthanides by solvent extraction

Abstract: The solvent extraction of trivalent actinides and lanthanides from aqueous 1M NaNO 3 by the sulfur containing acidic extractant Cyanex 301 was studied. This commercial extractant shows very interesting features for An(III)/Ln(III) separations depending on the purification of its main constituent bis(2,2,4-trimethylpentyl)dithiophosphinic acid. Efficient separations were observed with nonpurified Cyanex 301 for high Ln(III) concentrations, but not for low Ln(III) concentrations. Successful purification of Cyane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 3 publications
7
63
0
Order By: Relevance
“…It is known that these oxygen-containing organophosphoric compounds show high adsorbability for Ln~III!. 18,25,26 These separation experiments demonstrated that Am~III! can be effectively separated from a macro amount of Ln~III!…”
Section: Separation Behaviormentioning
confidence: 97%
See 3 more Smart Citations
“…It is known that these oxygen-containing organophosphoric compounds show high adsorbability for Ln~III!. 18,25,26 These separation experiments demonstrated that Am~III! can be effectively separated from a macro amount of Ln~III!…”
Section: Separation Behaviormentioning
confidence: 97%
“…compared to trivalent lanthanides, and the results agreed well with those reported in liquidliquid extraction. 16,18 On the other hand, the previous experiments indicated that 244 Cm~III! can also be extracted by purified Cyanex 301 and showed an extraction behavior similar to Am~III!~Ref.…”
Section: Adsorption Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…61 Repetition of the extraction experiments after two days and after 15 days showed a gradual decrease in SF values, which corresponds to gradual decomposition of CYANEX 301. Similar results were obtained by Hill et al 62 when the extraction experiments were carried out using synergistic mixtures (CYANEX 301 and TBP).…”
Section: Chart 26mentioning
confidence: 96%